2014
DOI: 10.5935/1676-4285.20144036
|View full text |Cite
|
Sign up to set email alerts
|

Communicative process in the emergency department between nursing staff and patients: social representations

Abstract: RESUME

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 12 publications
2
11
0
6
Order By: Relevance
“…Results from the current study show that only 68% of the participants communicated clearly and so provided complete information at a level that families could understand. This is similar to findings in a Brazilian study, in which Zani et al [29] found that communication between staff and families was not consistent. Communicating accurate information is essential in family-staff interactions as it enables families to exercise autonomy in decision-making.…”
Section: Relational Practices Interpersonal Skills Clustersupporting
confidence: 90%
“…Results from the current study show that only 68% of the participants communicated clearly and so provided complete information at a level that families could understand. This is similar to findings in a Brazilian study, in which Zani et al [29] found that communication between staff and families was not consistent. Communicating accurate information is essential in family-staff interactions as it enables families to exercise autonomy in decision-making.…”
Section: Relational Practices Interpersonal Skills Clustersupporting
confidence: 90%
“…Psychological support to patient families, who experience intensive stress and sorrow, may reduce their anxiety and fears (14). In sum, deciding whether the presence of family members is good or bad is a hard decision; it may vary according to cultural values and perspectives (19).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the focus of the professional is on the patient, which is important and necessary, however the family is placed on the side, which also shares and needs care (14,20) . Therefore, the promotion of the presence of the family in emergency procedures can be possible and accepted by the health professionals if there is a program/training of awareness of the team to allow the access in this context, and to annul the improvements given by the family in emergency care (8,19) . This training can be performed by the managers and professionals of the health unit itself in other that further expensive formative demands are not generated, and above all, that the professionals are integral part of the process of construction of an institutional identity that valorizes the families.…”
Section: Discussionmentioning
confidence: 99%
“…Under this spectrum, when questioned, the families of the patients in emergency care classify the necessity of shared information, the communication in timely manner, the support, and the proximity with relatives as their main priorities (7)(8) .…”
Section: Introductionmentioning
confidence: 99%